An alternative character education of “Warok” for the family: A local wisdom of Ponorogo community - Jauhan Budiwan (International Journal of Educational Studies in Social Sciences (IJESSS), 2021)
This research aimed to 1). Conceptual description of “Warok” content as family education to improve children's character; 2). To find out the steps of "Warok" as an educational alternative to the character values of children in Ponorogo; 3) To find out the effectiveness of "Warok" as character education in the community in Ponorogo. This research is an analysis of literature-based qualitative descriptive studies of the value of the local wisdom of the people of Ponorogo which is complemented by elements of social psychology of constructivism as an effort to maximize community character education. The results of this study indicate that “Warok” is educational teaching of the Ponorogo community that has developed in the community, which is formulated in 5 steps: Wani, Anulodho, Rumekso, Omber, Kulino, Warok as community education are very effective in improving children's character.